Odpowiedź :
Odpowiedź:
A) -2(x - 4)(x+3)
B) -1(x - 6)(x - 5)
C) 4(x - 0) (x-3)
4x(x-3)
D) 1(x + 2)(x - 2)
Szczegółowe wyjaśnienie:
A)
Δ =
postać kanoniczna
-2(x - 4)(x+3)
B)
[tex]f(x) = -x^{2} +11x - 30\\[/tex]
Δ = [tex]11^{2} - 4 * (-1) * (-30) = 121 - 120 = 1[/tex]
[tex]x_{1} =\frac{-11 -1}{2*(-1)} =\frac{-12}{-2} =6[/tex]
[tex]x_{2} = \frac{-11+1}{2*(-1)} = \frac{-10}{-2} = 5[/tex]
postać kanoniczna
-1(x - 6)(x - 5)
C)
[tex]f(x) = 4x^{2} - 12x\\x(4x-12) = 0\\x= 0, \\lub: 4x-12=0\\4x=12\\x=3[/tex]
postać kanoniczna
4(x - 0) (x-3)
4x(x-3)
D)
[tex]f(x) = -x^{2} +4\\-x^{2} = -4\\x^{2} = 4\\x_{1} = -2 \\ x_{2}=2[/tex]
postać kanoniczna
-1(x + 2)(x - 2)